Genetic and Environmental Determinants of T Helper 17 Pathogenicity in Spondyloarthropathies - Simone, Davide; Stingo, Alessia; Ciccia, Francesco (Frontiers in Genetics, 2021)
In Spondyloarthropathies (SpA), a common group of immune-mediated diseases characterised by excessive inflammation of musculoskeletal structures and extra-articular organs, T helper 17 (Th17) cells are widely considered the main drivers of the disease. Th17 are able to modulate their genes according to the immune environment: upon differentiation, they can adopt either housekeeping, anti-bacterial gene modules, or inflammatory, pathogenic functions, and only the latter would mediate immune diseases such as SpA. Experimental work aimed at characterising Th17 heterogeneity is largely performed on murine cells, for which the in vitro conditions conferring pathogenic potential have been identified and replicated. Interestingly, Th17 recognising different microorganisms are able to acquire specific cytokine signatures. An emerging area of research associates this heterogeneity to the preferential metabolic needs of the cell. In summary, the tissue environment could be determinant for the acquisition of pathogenetic features; this is particularly important at barrier sites such as the intestine, considered one of the key target organs in SpA, and likely a site of immunological changes that initiate the disease. In this review, we briefly summarise genetic, environmental and metabolic factors that could explain how homeostatic, anti-microbial Th17 could turn into disease-causing cells in Spondyloarthritis.